(untitled) (Modern education and development, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune disorder characterized by persistent joint inflammation and progressive bone erosion. Calcium therapy, often used to support bone health, has gained attention as a complementary approach in managing RA-related osteoporosis and bone mineral density loss. This review explores the potential benefits of calcium supplementation in RA patients, including its role in reducing fracture risk and supporting musculoskeletal function. However, concerns remain regarding optimal dosing, potential cardiovascular risks, and interactions with commonly prescribed RA medications. Clinical considerations for calcium use, including patient-specific factors and co-administration with vitamin D or other therapies, are discussed. Understanding the balance between efficacy and safety is essential for informed decision-making in the long-term management of RA patients.